PENGARUH PENDEKATAN TAKTIS DALAM MENINGKATKAN KETERAMPILAN BERMAIN BOLABASKET - Putriana Dwi Fadzriyah, - (2019)
The aim of this study is to find out how tactical approaches affect to improving basketball playing skills. The sampling technique in this study is Random Sampling. The sample in this study were students who joined extracurricular activities. This research method uses an experimental method with Pretest-Posttest Control Group Design. The instrument of this study was the GPAI with data analysis techniques used to answer the research questions by paired t-test. Based on the research findings and data analysis, the t value has a positive value of 2.515, with a probability value of 0.033 smaller (<) than 0.05. So based on the findings and data analysis, it can be concluded that the tactical approach has a positive influence on significantly increasing basketball playing skills.